The accounting features of disciplines of the cycle "Computer technologies" in the training students of engineering-pedagogic specialties - Gromov, E. V.; Yaschun, T. V. (Problems of Engineer-Pedagogical Education, 2018)
The practicability and rationality of using of the computer don`t induce any uncertainty long ago. Areas of its using are wide, it is a motivational stage of training, a part of training, a controlling activities and organization of feedback with student. The computer is actively using in research and organizational works of the teacher also. Consequently, every future teacher, which the students of engineering-pedagogical specialties appear, must be able to professionally use PC in their work. However, the using of such a powerful means of education has serious problems at the stage of knowledge by students of educational material, and organizational and methodological aspects. Consequently, future teachers should be prepared in advance to the difficulties of application of modern computer technologies in professional work. The authors try to lay out the basic problems that arise when using your computer with the appropriate software in the educational activity. Teacher, knowing described in the article "pitfalls", will try to minimize them and to organize the learning process with the use of a computer with the greatest efficiency.